Multiple Roles of HIV-1 Capsid during the Virus Replication Cycle - Novikova, Mariia (Virol Sin, 2019)
Human immunodeficiency virus-1 capsid (HIV-1 CA) is involved in different stages of the viral replication cycle. During virion assembly, CA drives the formation of the hexameric lattice in immature viral particles, while in mature virions CA monomers assemble in cone-shaped cores surrounding the viral RNA genome and associated proteins. In addition to its functions in late stages of the viral replication cycle, CA plays key roles in a number of processes during early phases of HIV-1 infection including trafficking, uncoating, recognition by host cellular proteins and nuclear import of the viral pre-integration complex. As a result of efficient cooperation of CA with other viral and cellular proteins, integration of the viral genetic material into the host genome, which is an essential step for productive viral infection, successfully occurs. In this review, we will summarize available data on CA functions in HIV-1 replication, describing in detail its roles in late and early phases of the viral replication cycle.